MISPERSEPSI DALAM PEMBACAAN MATAN SAFIINATUN NAJAAH (MISPERCEPTION IN READING MATAN SAFIINATUN NAJAAH) - Ufairoh, Shofi Najla; Sari, Dewi Masitoh Arum; Muassomah, Muassomah (Universitas Lambung Mangkurat, 2024)
AbstractMisperception in reading Matan Safiinatun Najaah. The process of encoding and decoding information can actually result in errors in understanding its meaning. Reading the book of Turats in Islamic boarding schools often experiences errors that can lead to misperceptions that result in a wrong understanding of religious teachings. The purpose of this study is to describe the forms, causes, and effects of misperceptions in reading Matan Safiinatun Najaah. This research method uses a qualitative-descriptive approach by conducting field observations. Data obtained through observation, tests, and documentation The research participants were seven female students at the Daruzzahra Ar-Rifa’i 2 Islamic Boarding School in Malang. The results showed that the reading of Matan Safiinatun Najaah by female students resulted in various errors and misperceptions. The findings of the tables in this article provide examples of misreadings such as errors in vowels and letters which have an impact on meaning errors. Misperceptions that occur in reading the book of Turats can have a negative impact, such as the spread of erroneous religious understanding or actions that are contrary to religious teachings. This research indicates that the reading of Matan Safiinatun Najaah in Islamic boarding schools often experiences errors and misperceptions. Increasing understanding of the scriptures and attention to the Arabic language can help avoid misperceptions. This article provides an explanation of the frequent reading errors and their impact, as well as an understanding of the importance of paying attention to context and Arabic when reading the book of Turats.Keywords: kitab Turats, Matan Safinatun Najaah, reading, misperceptions, pesantrenAbstrakMispersepsi dalam pembacaan Matan Safiinatun Najaah. Proses encoding dan decoding informasi ternyata dapat mengakibatkan kesalahan dalam memahami makna. Pembacaan kitab Turats di pondok pesantren tidak jarang mengalami kesalahan yang dapat menyebabkan mispersepsi yang berdampak pada pemahaman yang salah tentang ajaran agama. Tujuan penelitian ini adalah untuk memaparkan bentuk, penyebab, dan dampak mispersepsi dalam pembacaan Matan Safiinatun Najaah. Metode penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan melakukan observasi lapangan. Data diperoleh melalui observasi, tes, dan dokumentasi. Partisipan penelitian adalah tujuh santriwati di Pondok Pesantren Daruzzahra Ar-Rifa’i 2 Malang. Hasil penelitian menunjukkan bahwa pembacaan Matan Safiinatun Najaah oleh santriwati menghasilkan bermacam-macam kesalahan dan mispersepsi. Temuan tabel-tabel dalam artikel ini memaparkan contoh kesalahan pembacaan seperti kesalahan dalam harakat dan huruf yang berdampak pada kesalahan makna. Mispersepsi yang terjadi dalam pembacaan kitab Turats dapat berdampak negatif, seperti penyebaran pemahaman agama yang keliru atau tindakan yang bertentangan dengan ajaran agama. Dari hasil penelitian ini, penulis menemukan bahwa pembacaan Matan Safiinatun Najaah di pondok pesantren tidak jarang mengalami kesalahan dan mispersepsi. Meningkatkan pemahaman terhadap kitab dan perhatian terhadap bahasa Arab dapat membantu menghindari terjadinya mispersepsi. Artikel ini memberikan paparan tentang kesalahan pembacaan yang sering terjadi dan dampaknya serta memberikan pemahaman tentang pentingnya memperhatikan konteks dan bahasa Arab dalam membaca kitab Turats.Kata-kata kunci: kitab Turats, Matan Safiinatun Najaah, membaca, mispersepsi, pesantren